The Role of Islamic Education Teachers in Shaping Students' Morality: A Theoretical Analysis - Danyalin Mohammad Mafakhir (Jurnal Penelitian Medan Agama, 2025)
The role of Islamic Education (PAI) teachers is crucial in shaping students' character, as they not only serve as central figures but also bear the primary responsibility of educating, teaching, guiding, and training students to become faithful, God-fearing, knowledgeable, virtuous, and responsible individuals. Moral strengthening is the core focus of Islamic education, which requires a deep understanding of character and moral values as well as the application of appropriate strategies and methods to foster positive character development. This study employs a qualitative approach through library research to identify the role of Islamic Education teachers in character formation and to analyze their efforts in reinforcing moral values. The findings reveal that PAI teachers act as role models in instilling religious values and moral understanding, while also guiding students to develop social awareness, empathy, and good conduct. Consequently, moral strengthening is considered a strategic solution to address the ongoing moral crisis, particularly in Indonesia.